Feeding behavior of Simulium vittatum larvae in response to various suspended materials: implications for control using biological larvicides. Issue 1 (11th March 2016) - Iburg, Joseph P.; Gray, Elmer W.; Noblet, Raymond
Abstract: Biologically based larvicides used to suppress nuisance populations of black flies (Diptera: Simuliidae) require that the larvae ingest the larvicide for mortality to occur. Materials present in the habitat that alter larval feeding behavior may reduce the effectiveness of the larvicide. This study was conducted to determine the effects that commonly occurring materials in larval habitats have on Simulium vittatum Zetterstedt feeding behavior. Larvae were exposed to 50 p.p.m. of kaolinite clay and 4 p.p.m. of purified diatom frustules. Larvae were also exposed to 10 000 cells or colonies per ml of viable green algae, Chlorella vulgaris Pratt and Scenedesmus quadricauda (Turp) Bréb, and the diatom Cyclotella meneghiniana Kützing to determine the effects that these materials have on larval feeding behavior. Individual larvae were recorded using a digital camcorder to determine the average number of times the larvae extended and retracted their cephalic fans per min (flick rate) in each medium. Following exposure to the selected material, neon red particles (NRP) (DayGlo) were added to the larval medium for 20 min. A spectrophotometric analysis was conducted to determine the average quantity of NRP consumed by larvae per min in each medium. The flick rate and quantity of NRP consumed by larvae was not significantly affected by clay material or viable Chlorella cells. When Scenedesmus colonies or Cyclotella cells were present in the larval medium, larval flick rate and NRP ingestion was significantly reduced. The presence of diatom frustules in the medium resulted in the most severe reduction in larval flick rate and NRP ingestion. The results suggest that larval flick rate can change depending on environmental conditions, and that suppression programs using biologically based larvicides may benefit from investigating the potential correlation between algal counts and treatment efficacy.